Reinventing access - Reed , Barbara (Archives & Manuscripts, 2014)
In 1989 David Bearman threw virtual bombs at the practices of the archival profession. In Australia we responded to the emerging issues of digital recordkeeping influenced by Bearman’s challenging analysis. However, access has long been an area somewhat neglected within the Australian recordkeeping profession. Addressing this is core to reconceptualising the access function for the future in the digital environment.